2023
DOI: 10.1038/s41538-023-00205-2
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of meat floss origin using a supervised machine learning-based electronic nose towards food authentication

Abstract: Authentication of meat floss origin has been highly critical for its consumers due to existing potential risks of having allergic diseases or religion perspective related to pork-containing foods. Herein, we developed and assessed a compact portable electronic nose (e-nose) comprising gas sensor array and supervised machine learning with a window time slicing method to sniff and to classify different meat floss products. We evaluated four different supervised learning methods for data classification (i.e., lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…For the input samples, to determine whether the root node of the decision tree is a leaf node, if it is the case, then return to the average value of the sample target variable in the current leaf; if not, compare the segmentation variable and segmentation value of this node with the value of the corresponding sample variable. If the value of the sample variable is not larger than the cutoff value of this node, the visit to the left child of this node is continued; if the value of the sample variable is larger than the cutoff value of this node, the visit to the right child of this node is performed, and so on, until the leaf node is visited, and finally, the average value of the sample target variable of the leaf node is returned [31]. In building the RF model, a quantitative prediction model of endomorphic components was established using the results of dimensionality reduction in image information (color and texture) by using different principal components and 20 N-values (50-1000, with a step size of 50) as inputs, and catechin fractions and thearubigin content as outputs [32].…”
Section: Prediction Results Of the Catechin Fraction And Thearubigin ...mentioning
confidence: 99%
“…For the input samples, to determine whether the root node of the decision tree is a leaf node, if it is the case, then return to the average value of the sample target variable in the current leaf; if not, compare the segmentation variable and segmentation value of this node with the value of the corresponding sample variable. If the value of the sample variable is not larger than the cutoff value of this node, the visit to the left child of this node is continued; if the value of the sample variable is larger than the cutoff value of this node, the visit to the right child of this node is performed, and so on, until the leaf node is visited, and finally, the average value of the sample target variable of the leaf node is returned [31]. In building the RF model, a quantitative prediction model of endomorphic components was established using the results of dimensionality reduction in image information (color and texture) by using different principal components and 20 N-values (50-1000, with a step size of 50) as inputs, and catechin fractions and thearubigin content as outputs [32].…”
Section: Prediction Results Of the Catechin Fraction And Thearubigin ...mentioning
confidence: 99%
“…Many studies demonstrated the widespread use of e-nose in assessing food quality-related properties, including the detection of Salmonella (Gonçalves et al, 2023), the quality status of fruits (Buratti et al, 2018;Qiu et al, 2014Qiu et al, , 2015, the quality of oils (Hosseini et al, 2023), and the detection of contaminated foods (Feyzioglu & Taspinar, 2023;Putri et al, 2023;Tian et al, 2023Tian et al, ). et al, 2019.…”
Section: Figurementioning
confidence: 99%